Synthetic method for liquid crystal film on surface of metal component
By preparing a titanium-aluminum-tungsten metal wire mesh on the surface of the metal component and forming a liquid crystal film, the problem of poor wear resistance on the surface of the metal component is solved, and the effect of improving impact resistance and reducing processing costs is achieved.
Patent Information
- Application Number
- CN202411500250.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
Due to the dual influence of dynamic load and aggressive environment, microcracks and oxide films are easily formed on the surface of metal components, resulting in poor wear resistance and affecting the reliability and service life of the components.
A synthesis method for the liquid crystal film on the surface of metal components is adopted, and a titanium-aluminum-tungsten metal wire mesh is prepared by the combined use of a ball milling tank and liquid nitrogen, and a liquid crystal film is formed through a thermal explosion reaction to improve the impact resistance of the metal components.
In a short time, a liquid crystal film with a large thickness is formed on the surface of the metal component, which significantly improves the impact resistance of the metal component and reduces processing costs.
Smart Images

Figure CN119876944A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for synthesizing a liquid crystal film on the surface of a metal component, and relates to the technical field of processing and manufacturing annular block materials. Background Art
[0002] With the continuous improvement of the mechanical properties of metal components, structural weight reduction is a major driving force, but different metal surfaces have different wear resistance, and this characteristic cannot be solved by mechanical properties, such as titanium alloy replacing high-strength steel, magnesium alloy replacing titanium alloy, etc. The life of metal components depends largely on the reliability of metal components, because under the dual influence of dynamic loads and corrosive environments, microcracks containing different metal oxide films will form on the metal surface, which is particularly serious on non-ferrous metals.
[0003] At present, the research on the wear resistance of metal surfaces mainly focuses on gradient changes in composition and surface modification, but these methods often change the organizational structure of the matrix itself. Recently, foreign researchers have been committed to forming a liquid crystal protective layer on the metal surface at room temperature to improve the wear resistance of the metal surface, because liquid crystal is an ideal fiber precursor, and it is used on turbine blades to improve its reliability. The liquid crystal film contacts the entire surface of the nozzle blades and the hard-to-reach microcracks, thereby achieving the effect of completely removing metal oxides. This technology can effectively reduce the repair time of waste blades of gas turbine engines, increase the service life of turbine blades after cleaning, and reduce the amount of waste in its maintenance, thereby providing technical support for cleaning the surface and microcracks of gas turbine engine blades. Summary of the invention
[0004] The present invention is designed to address the above-mentioned existing technical situation and provides a method for synthesizing a liquid crystal film on the surface of a metal component. Its purpose is to be able to form a thicker liquid crystal film on the surface of the metal component in a short time, improve the impact resistance of the metal component, and significantly reduce processing costs.
[0005] To implement the above purpose, the technical solution of the present invention is as follows:
[0006] The steps of the synthesis method of the liquid crystal film on the surface of the metal component proposed by the technical solution of the present invention are as follows:
[0007] Step 1: Raw material preparation
[0008] The raw materials include titanium powder, aluminum powder, tungsten powder and a steel pipe 11, wherein the powder particle size is -350 mesh to -450 mesh, the purity is 99.99%, and the surface roughness of the outer surface of the steel pipe after mechanical processing is not greater than 1.6 to form friction and adhesion, and then the outer surface of the steel pipe is fully cleaned;
[0009] Step 2: Device preparation
[0010] The device comprises a cylindrical ball mill 1, which can rotate along a central axis 4 and is connected to a heating device for heating. The side wall of the ball mill 1 is provided with inwardly inclined protruding blades 2, and through holes 3 are processed between the protruding blades 2. The diameter of the through holes 3 is 100-1000nm.
[0011] Another cylindrical fixed shell 5 is arranged on the periphery of the fixed shell 5, and the side wall of the fixed shell 5 is a sandwich structure, which is filled with liquid nitrogen 6. The ball mill 1 and the two ends of the shell 5 are sealed by top covers 7. Insertion holes 8 are processed at the top covers 7 at both ends of the shell 5. The steel pipe 11 can be placed in the synthetic space 10 formed by the inner wall of the shell 5 and the side wall of the ball mill 1 through the two insertion holes 8;
[0012] Step 3: Preparation of titanium liquid wire with tungsten powder particles
[0013] Put titanium powder into the ball mill 1, and make the ball mill 1 start to rotate clockwise at a speed of 50-200 rad / s. After maintaining for 15-30 minutes, the titanium powder is broken by colliding with the protruding blades 2 on the inner wall of the ball mill 1 and colliding with each other. Then put tungsten powder in the synthesis space 10, and fill the sandwich structure of the side wall of the fixed shell 5 with liquid nitrogen 6. At the same time, start the heating device to heat the ball mill 1 at a heating temperature of 1000-1200°C, and then increase the rotation speed of the ball mill 1 to 300-500 rad / s. At this time, the titanium powder accelerates the collision in the ball mill 1. After maintaining for 10-30 minutes, the rotation direction of the ball mill 1 is changed to counterclockwise. At this time, due to the effect of inertia, the titanium powder is further cut by the protruding blades 2 on the inner wall of the ball mill 1. Then, under the action of centrifugal force, the titanium powder enters the synthesis space 10 in liquid filaments through the through hole 3, and then its surface will adhere to the tungsten powder particles dispersed in the synthesis space 10;
[0014] Step 4: Weaving of titanium wire mesh on the surface of steel tube 11
[0015] Continue to maintain the operating state of step 3, insert the steel pipe 11 from the insertion hole 8 above the synthetic space 10
[0016] Insert and pass through the insertion hole 8 below the synthesis space 10, so that the surface to be processed in the middle of the steel pipe 11 is in the synthesis space 10, and the steel pipe 11 is rotated at the same time. At this time, the liquid metal wire formed in step 3 is rapidly cooled and wound around the surface of the steel pipe 11 under the action of the liquid nitrogen 6 in the side wall of the fixed shell 5, and is woven into a titanium metal wire mesh;
[0017] Step 5: Weaving of aluminum wire mesh on the surface of steel pipe 11
[0018] Another ball mill 1 filled with aluminum powder is used to replace the ball mill 1 filled with titanium powder, and the above steps 3 and 4 are repeated, except that the heating temperature of the ball mill 1 is adjusted to 700-900° C., and an aluminum wire mesh is woven on the titanium wire mesh;
[0019] Step 6: Weaving of titanium-aluminum-tungsten metal mesh on the surface of the steel tube 11
[0020] According to the design requirements, the above steps 3 to 5 are repeated, and finally a titanium-aluminum-tungsten metal mesh is obtained on the surface of the steel tube 11;
[0021] Step 7: Preparation of liquid crystal film
[0022] A steel tube 11 with a titanium-aluminum-tungsten metal wire mesh on its surface is placed on a lathe, and the steel tube 11 is rapidly heated by a pulse current at a heating rate of 100-200°C / s. When the temperature reaches 1300-1500°C, it is maintained for 8-10s and the heating is stopped. At this time, the titanium and aluminum in the titanium-aluminum-tungsten metal wire mesh are melted, and a thermal explosion reaction occurs partially. The holes produced by the thermal explosion reaction are filled by the molten titanium and aluminum. After cooling, the steel tube 11 with a liquid crystal film can be obtained.
[0023] During implementation, the material of the steel pipe in step 1 is high-strength steel with a grade of 4340.
[0024] In addition, the protruding edge 2 described in step 2 is in the shape of fish scales.
[0025] In addition, in the device of step 2, a transverse insertion hole 9 is processed on the side wall of the shell 5 so that the top end portion of the steel pipe 11 can pass through the transverse insertion hole 9 and penetrate into the synthetic space.
[0026] During implementation, in step six, in the titanium-aluminum-tungsten metal mesh structure made on the surface of the steel tube 11, the metal wires between adjacent metal wire meshes are vertically overlapped.
[0027] The characteristics and beneficial effects of the technical solution of the present invention are:
[0028] 1. The technical solution of the present invention is different from the spraying and coating methods. The composition design of the liquid crystal film obtained by this method is more flexible, and the initial state of the film is powder;
[0029] Second, the liquid crystal film in the technical solution of the present invention is a mesh structure before molding, such a structure is not easy to fall off, different metal wires cross each other, resulting in an interface reaction, high adhesion; high bonding strength,
[0030] 3. The ball mill in the technical solution of the present invention can not only crush the powder particles, but also realize the forming output of the liquid metal wire through its self-rotation and heating functions, and then through the effect of the cold field in its peripheral synthetic space, a titanium-aluminum-tungsten metal wire mesh with a stable filament shape, uniform diameter, more orderly arrangement and higher filling density is obtained on the metal surface, and the forming thickness can be greatly increased in a short time. In the subsequent liquid crystal film formation process, the liquid metal formed by the titanium-aluminum-tungsten metal wire mesh is more likely to flow to the structural dead zone and fill defects such as microcracks;
[0031] 4. Compared with magnetron sputtering and vapor deposition methods, the cost of the liquid crystal film formed by the technical solution of the present invention can be reduced by 40%, and the forming device is relatively simple, which can be applied to a variety of metal components and liquid crystal film composition designs. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a structural schematic diagram of the device described in the technical solution of the present invention DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments:
[0034] The steps of preparing a liquid crystal film on the surface of a metal component by using the technical solution of the present invention are as follows:
[0035] Step 1: Raw material preparation
[0036] The raw materials include titanium powder, aluminum powder, tungsten powder and a steel pipe 11 of high-strength steel with a material grade of 4340, wherein the powder particle size is -350 mesh to -450 mesh, the purity is 99.99%, and the surface roughness of the outer surface of the steel pipe after mechanical processing is not greater than 1.6 to form friction and adhesion, and then the outer surface of the steel pipe is fully cleaned;
[0037] Step 2: Device preparation
[0038] See attached Figure 1 As shown, the device includes a cylindrical ball mill 1, which can rotate along a central axis 4 and is connected to a heating device for heating. The side wall of the ball mill 1 is provided with inwardly inclined fish-scale-shaped protruding blades 2, and through holes 3 are processed between the protruding blades 2. The diameter of the through holes 3 is 100-1000nm; another cylindrical fixed shell 5 is arranged on the periphery of the ball mill 1, and the side wall of the fixed shell 5 is a sandwich structure, which is filled with liquid nitrogen 6. The ball mill 1 and the two ends of the shell 5 are sealed by a top cover 7 to seal their internal space, and the top covers 7 at both ends of the shell 5 are processed with insertion holes 8. The steel pipe 11 can be placed in a synthetic space 10 formed by the inner wall of the shell 5 and the side wall of the ball mill 1 in a through manner through the two insertion holes 8.
[0039] In addition, a transverse insertion hole 9 is processed on the side wall of the housing 5 so that the top end portion of the steel pipe 11 can penetrate into the synthetic space through the transverse insertion hole 9;
[0040] Step 3: Preparation of titanium liquid wire with tungsten powder particles
[0041] Put titanium powder into the ball mill 1, and make the ball mill 1 start to rotate clockwise at a speed of 50-200 rad / s. After maintaining for 15-30 minutes, the titanium powder is broken by colliding with the protruding blades 2 on the inner wall of the ball mill 1 and colliding with each other. Then put tungsten powder in the synthesis space 10, and fill the sandwich structure of the side wall of the fixed shell 5 with liquid nitrogen 6. At the same time, start the heating device to heat the ball mill 1 at a heating temperature of 1000-1200°C, and then increase the rotation speed of the ball mill 1 to 300-500 rad / s. At this time, the titanium powder accelerates the collision in the ball mill 1. After maintaining for 30-1min, the rotation direction of the ball mill 1 is changed to counterclockwise. At this time, due to the effect of inertia, the titanium powder is further cut by the protruding blades 2 on the inner wall of the ball mill 1. Then, under the action of centrifugal force, the titanium powder enters the synthesis space 10 in liquid filaments through the through hole 3, and then its surface will adhere to the tungsten powder particles dispersed in the synthesis space 10;
[0042] Step 4: Weaving of titanium wire mesh on the surface of steel tube 11
[0043] Continue to maintain the operating state of step 3, insert the steel pipe 11 from the insertion hole 8 above the synthetic space 10
[0044] Insert and pass through the insertion hole 8 below the synthesis space 10, so that the surface to be processed in the middle of the steel pipe 11 is in the synthesis space 10, and the steel pipe 11 is rotated at the same time. At this time, the liquid metal wire formed in step 3 is rapidly cooled and wound around the surface of the steel pipe 11 under the action of the liquid nitrogen 6 in the side wall of the fixed shell 5, and is woven into a titanium metal wire mesh;
[0045] Step 5: Weaving of aluminum wire mesh on the surface of steel pipe 11
[0046] Another ball mill 1 filled with aluminum powder is used to replace the ball mill 1 filled with titanium powder, and the above steps 3 and 4 are repeated, except that the heating temperature of the ball mill 1 is adjusted to 700-900° C., and an aluminum wire mesh is woven on the titanium wire mesh;
[0047] Step 6: Weaving of titanium-aluminum-tungsten metal mesh on the surface of the steel tube 11
[0048] According to the design requirements, the operations of steps 3 to 5 are repeated, and finally a titanium-aluminum-tungsten metal mesh is obtained on the surface and both ends of the steel tube 11. In the titanium-aluminum-tungsten metal mesh structure obtained on the surface of the steel tube 11, the metal wires between adjacent metal meshes are vertically overlapped;
[0049] Step 7: Preparation of liquid crystal film
[0050] A steel tube 11 with a titanium-aluminum-tungsten metal wire mesh on its surface is placed on a lathe, and the steel tube 11 is rapidly heated by a pulse current at a heating rate of 100-200°C / s. When the temperature reaches 1300-1500°C, it is maintained for 8-10s and the heating is stopped. At this time, the titanium and aluminum in the titanium-aluminum-tungsten metal wire mesh are melted, and a thermal explosion reaction occurs partially. The holes produced by the thermal explosion reaction are filled by the molten titanium and aluminum. After cooling, the steel tube 11 with a liquid crystal film can be obtained.
Claims
1. A method for synthesizing a liquid crystal film on the surface of a metal component, characterized in that: The steps of this method are as follows: Step 1: Raw material preparation The raw materials include titanium powder, aluminum powder, tungsten powder and a steel pipe (11), wherein the powder particle size is -350 mesh to -450 mesh, the purity is 99.99%, and the surface roughness of the outer surface of the steel pipe after mechanical processing is not greater than 1.6 to form friction and adhesion, and then the outer surface of the steel pipe is fully cleaned; Step 2: Device preparation The device comprises a cylindrical ball mill (1), which can rotate along a central axis (4) and is connected to a heating device for heating. The side wall of the ball mill (1) is provided with inwardly inclined protruding blades (2), and through holes (3) are processed between the protruding blades (2). The diameter of the through holes (3) is 100-1000 nm. Another cylindrical fixed shell (5) is arranged on the periphery of the ball mill (1). The side wall of the fixed shell (5) is a sandwich structure filled with liquid nitrogen (6). The internal spaces of the ball mill (1) and the two ends of the shell (5) are sealed by top covers (7). Insertion holes (8) are processed at the top covers (7) at the two ends of the shell (5). The steel pipe (11) can be placed in the middle part of the steel pipe (11) through the two insertion holes (8) in a through manner in the synthetic space (10) formed by the inner wall of the shell (5) and the side wall of the ball mill (1). Step 3: Preparation of titanium liquid wire with tungsten powder particles Titanium powder is placed in a ball mill (1), and the ball mill (1) starts to rotate clockwise at a speed of 50-200 rad / s. After maintaining for 15-30 minutes, the titanium powder is crushed by colliding with the protruding blades (2) on the inner wall of the ball mill (1) and colliding with each other. Then, tungsten powder is placed in the synthesis space (10), and liquid nitrogen (6) is filled in the sandwich structure of the side wall of the fixed shell (5). At the same time, the heating device is started to heat the ball mill (1) at a heating temperature of 1000-1200°C. The rotation speed of the ball mill (1) is increased to 300-500 rad / s, at which time the titanium powder is accelerated to collide in the ball mill (1). After maintaining the speed for 10-30 minutes, the rotation direction of the ball mill (1) is changed to counterclockwise. At this time, due to the effect of inertia, the titanium powder is further cut by the protruding blade (2) on the inner wall of the ball mill (1). Then, under the effect of centrifugal force, the titanium powder passes through the through hole (3) in the form of liquid filaments and enters the synthesis space (10). Then, the titanium powder surface will adhere to the tungsten powder particles dispersed in the synthesis space (10); Step 4: Weaving of titanium wire mesh on the surface of the steel tube (11) Continue to maintain the operating state of step 3, insert the steel pipe (11) through the insertion hole (8) above the synthetic space (10) Inserting and passing through the insertion hole (8) below the synthesis space (10), so that the surface to be processed in the middle of the steel pipe (11) is located in the synthesis space (10), and the steel pipe (11) is rotated at the same time, at which time the liquid metal wire formed in step 3 is rapidly cooled and wound around the surface of the steel pipe (11) under the action of the liquid nitrogen (6) in the side wall of the fixed shell (5), and is woven into a titanium metal mesh; Step 5: Weaving of aluminum wire mesh on the surface of the steel pipe (11) Another ball mill (1) filled with aluminum powder is used to replace the ball mill (1) filled with titanium powder, and the operations of steps 3 and 4 are repeated, except that the heating temperature of the ball mill (1) is adjusted to 700-900° C., and an aluminum wire mesh is woven on the titanium wire mesh; Step 6: Weaving of titanium-aluminum-tungsten metal mesh on the surface of the steel pipe (11) According to the design requirements, the operations of steps 3 to 5 are repeated, and finally a titanium-aluminum-tungsten metal mesh is obtained on the surface of the steel tube (11); Step 7: Preparation of liquid crystal film A steel tube (11) with a titanium-aluminum-tungsten metal mesh on its surface is placed on a lathe, and the steel tube (11) is rapidly heated by a pulse current at a heating rate of 100-200°C / s. When the temperature reaches 1300-1500°C, it is maintained for 8-10s and the heating is stopped. At this time, the titanium and aluminum in the titanium-aluminum-tungsten metal mesh are melted and partially undergo a thermal explosion reaction. The holes produced by the thermal explosion reaction are filled by the molten titanium and aluminum. After cooling, a steel tube (11) with a liquid crystal film can be obtained.
2. The method for synthesizing a liquid crystal film on the surface of a metal component according to claim 1, characterized in that: The material of the steel pipe in step 1 is high-strength steel with a grade of 4340.
3. The method for synthesizing a liquid crystal film on a metal component surface according to claim 1, characterized in that: The protruding blade (2) described in step 2 is in the shape of fish scales.
4. The method for synthesizing a liquid crystal film on a metal component surface according to claim 1, characterized in that: In the device of step 2, a transverse insertion hole (9) is processed on the side wall of the shell (5) so that the top end portion of the steel pipe (11) can penetrate into the synthetic space through the transverse insertion hole (9).
5. The method for synthesizing a liquid crystal film on a metal component surface according to claim 1, characterized in that: In step six, in the titanium-aluminum-tungsten metal mesh structure made on the surface of the steel tube (11), the metal wires between adjacent metal wire meshes are vertically overlapped.